Garlic decreases liver and kidney receptor for advanced glycation end products expression in experimental diabetes. Issue 2 (June 2016) - Al-Qattan, Khaled K.; Mansour, Mohamed H.; Thomson, Martha; Ali, Muslim
Abstract: The up-regulation of the receptor for advanced glycation end products (RAGE) has been implicated as a major mediator in the development and progression of diabetic nephropathy and hepatic fibrogenesis. The present study was designed to investigate the potential of garlic ( Allium sativum L.) to modulate the level of expression of RAGE in renal and hepatic tissues of diabetic rats. Three groups of rats were studied after 8 weeks following diabetes induction: normal, streptozotocin-induced diabetic (control diabetic), and garlic-treated diabetic rats. A polyclonal antibody of proven specificity to RAGE indicated in immunohistochemical assays that RAGE labeling was significantly increased in renal and hepatic tissues of control diabetic rats compared to the normal group. The increased RAGE labeling involved mesangial cells in glomeruli exhibiting signs of mesangial expansion, mesangial nodule formation and glomerulosclerosis. In the liver, a significant up-regulation of RAGE was observed in hepatocytes and bile ducts and vessels in portal tracts. In 2-dimensional Western blots, RAGE expression in both tissues was dominated by heterogeneous charge variants, represented by 46–50 kDa isoforms with more basic pIs compared to their counterparts in normal rats. Compared to control diabetic rats, RAGE labeling in the garlic-treated diabetic group was significantly reduced throughout renal and hepatic regions and was marked by the expression of 43–50 kDa acidic charge variants comparable to those observed in normal rats. The capacity of garlic to modulate diabetes-induced up-regulation of selective RAGE polymorphic variants may be implicated in attenuating the detrimental consequences of excessive RAGE signaling manifested by diabetes-associated disorders.